Society Intention in Distribution of Zakat, Infaq and Shadaqah (ZIS) through the Use of Crowdfunding Platform - Gina Destrianti Karmanto; A. Jajang W. Mahri; Aas Nurasyiah (Universitas Muhammadiyah Malang, 2021)
One of the strategy of collecting zakat, infaq, and shodaqoh (ZIS) fund is through digital collection. However, the community's intention to distribute zakat, infaq and shodaqoh through the crowdfunding platform have increased. The purpose of this study is to discover the Technology Acceptance Model (TAM) and trust theory by analyzing what factors influence the intention of the Indonesian people to channel zakat, infaq and shodaqoh through the use of a crowdfunding platform. The population in this study are people who have used digital payment platforms with a sample of population 385 respondents. This study uses data analysis techniques with the Patrial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results found that society intention in distribution of zakat, infaq and shadaqah (ZIS) through the use of crowdfunding platform afected by perceived ease of use, perceived usefulness and trust. This research is expected to provide benefits about policies to increase behavioral intention to distribute zakat, infaq and Shodaqoh through the use of crowdfunding platforms.